2009
DOI: 10.1523/jneurosci.0362-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling between mGluR1 and Cav3.1 T-Type Calcium Channels Contributes to Parallel Fiber-Induced Fast Calcium Signaling within Purkinje Cell Dendritic Spines

Abstract: T-type voltage-gated calcium channels are expressed in the dendrites of many neurons, although their functional interactions with postsynaptic receptors and contributions to synaptic signaling are not well understood. We combine electrophysiological and ultrafast two-photon calcium imaging to demonstrate that mGluR1 activation potentiates cerebellar Purkinje cell Ca v 3.1 T-type currents via a G-protein-and tyrosine-phosphatase-dependent pathway. Immunohistochemical and electron microscopic investigations on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
137
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 71 publications
10
137
0
Order By: Relevance
“…Although KCCN4 mRNA has been detected in the cerebellar Purkinje cell layer (23), KCa3.1 expression has not been reported in CNS neurons (3). Of the three Cav3 channel isoforms expressed in Purkinje cells (13,14,24), Cav3.2 is preferentially blocked by 100 μM Ni 2+ (16), as found for the evoked AHP (Fig. 1A).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Although KCCN4 mRNA has been detected in the cerebellar Purkinje cell layer (23), KCa3.1 expression has not been reported in CNS neurons (3). Of the three Cav3 channel isoforms expressed in Purkinje cells (13,14,24), Cav3.2 is preferentially blocked by 100 μM Ni 2+ (16), as found for the evoked AHP (Fig. 1A).…”
Section: Resultsmentioning
confidence: 63%
“…As a result, parallel fiber-evoked EPSPs surpassed spike threshold within 5-10 stimuli to reliably generate spike output. We found no role for mGluR1 receptor activation (14) or presynaptic endocannabinoid receptors (32), as neither JNJ16259685 nor the CB1 receptor blocker AM-251 occluded the effect of Ni 2+ (n = 4) during these stimuli. In addition, the parallel fiber-evoked EPSP paired-pulse ratio was unaffected by either Ni 2+ (n = 7, P = 0.95) or TRAM-34 (n = 7, P = 0.582) (Fig.…”
Section: Cav3-kca31 Interaction Controls Temporal Summation Of Parallelmentioning
confidence: 88%
See 1 more Smart Citation
“…The biophysical properties of low-voltage activated calcium channels allow them to be activated by subthreshold synaptic inputs and thus participate in synaptic integration and signaling. Indeed, we have previously shown that T-type channels are activated by synaptic activity at the PF-PC synapse (11,22). Furthermore, they can contribute to the intrinsic firing behavior of neurons (23,24).…”
Section: T-type Channel Blockade Prevents Ltp Induction With No Effecmentioning
confidence: 98%
“…PCs bear different voltage-dependent Ca channels including P/Q-type (6)(7)(8) and T-type channels (9,10). The spines of PCs contain a high density of Ca V 3.1 T-type channels (11), which can be readily activated by typical bursts of PF activity that occur during sensory stimulation (12)(13)(14). To date, the function of the PF to PC synapse plays a pivotal role in cerebellar motor learning, probably involving bidirectional changes of its strength (1)(2)(3).…”
mentioning
confidence: 99%